2018
DOI: 10.1159/000489166
|View full text |Cite
|
Sign up to set email alerts
|

Grape Leucoanthocyanidin Protects Liver Tissue in Albino Rabbits with Nonalcoholic Hepatic Steatosis

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a common ailment. It is usually found in association with diabetes or obesity. There are no approved drugs to treat this condition. The study of flavonoid consumption has increased over the decades due to their antioxidative properties, although the literature is scarce when it comes to their effects in liver tissue. The purpose of this study was to evaluate the role of leucoanthocyanidin in nonalcoholic hepatic steatosis. Thirty male albino rabbits were divided in 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…This is very consistent with our investigations. In a study on the rabbit model of NAFLD, the authors investigated flavonoid from grape and they reported a promising effect in minimising histological signs of NAFLD [ 85 ], and this supports our study in terms of role of natural flavonoids in protection against NAFLD. In a study using mice NAFLD model, the authors investigated the protective effect of blue honeysuckle extract against NAFLD; they characterised that extract as rich in polyphenols and showed hepatoprotective results against NAFLD, explored the antioxidant mechanism, and assigned it as the most likely underlying protective mechanism [ 70 ].…”
Section: Discussionsupporting
confidence: 87%
“…This is very consistent with our investigations. In a study on the rabbit model of NAFLD, the authors investigated flavonoid from grape and they reported a promising effect in minimising histological signs of NAFLD [ 85 ], and this supports our study in terms of role of natural flavonoids in protection against NAFLD. In a study using mice NAFLD model, the authors investigated the protective effect of blue honeysuckle extract against NAFLD; they characterised that extract as rich in polyphenols and showed hepatoprotective results against NAFLD, explored the antioxidant mechanism, and assigned it as the most likely underlying protective mechanism [ 70 ].…”
Section: Discussionsupporting
confidence: 87%
“…Vaccinium myrtillus Dp, cy, pt, Pn, Mv ↓Dyslipidemia ↓Gut microbiome dysbiosis [33] Lonicera caerulea C3G ↓Hepatic lipid metabolic gene expression ↑AMPK ↑ACC [34] Vitis vinifera leucoanthocyanidin ↑Antioxidant [35] Fragaria x ananassa C3G, C3R, Pt-3-G ↑Autophagy [36] Alcoholic Fatty Liver Disease…”
Section: Hypercholesterolemiamentioning
confidence: 99%
“…C3G, an anthocyanin primarily extracted from honeyberry (Lonicera caerulea), might resist hepatic steatosis by targeting AMPK-mediated fatty acid metabolism in the liver [34]. Franklin et al, demonstrated that grape leucoanthocyanidin can prevent NAFLD through its antioxidant properties [35]. In addition, cherry anthocyanins exert positive effects against OA-induced hepatic lipid accumulation by activating autophagy [36].…”
Section: Diseases Of the Digestive System 231 Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Anthocyanins and anthocyanins-rich foods extracts or juices have demonstrated in several studies their ability to reduce the hepatic content of TG and lipids [ 85 , 86 ] and their capacity to modulate hepatic metabolism to protect against NAFLD [ 62 , 87 , 88 , 89 ]. Although in most of the published approaches performed with rodent models of obesity or NAFLD, anthocyanins or anthocyanin-rich fruits or extracts significatively reduced the hepatic lipid content and ameliorated the hepatic steatosis profile of these animals [ 88 , 90 , 91 , 92 ] some ineffective approaches have also been described [ 93 , 94 , 95 ].…”
Section: Anthocyaninsmentioning
confidence: 99%